SPECIFICITY OF TRANSACTION COSTS IN THE SPHERE OF EDUCATION IN THE EMERGING KNOWLEDGE ECONOMY - A. G. Furin (Модернизация, инновация, развитие)
The paper considers the specifics of transaction costs in the sphere of education. Comparative analysis of the theoretical framework of the research devoted to the theory of transaction costs, allowed us to determine the causes and types of transaction costs in the educational environment. On the basis of the existing conceptual framework and specifics of the education system the paper formulates the definition of transaction costs and their classification is given on the basis of the principle of legality. The conclusion is that the minimization of the «illegal» costs is possible through the creation of information management system within the education cluster.